2017
DOI: 10.1186/s11671-016-1815-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of InGaAs/InAlAs Avalanche Photodiodes

Abstract: In this paper, we report a two-dimensional (2D) simulation for InGaAs/InAlAs separate absorption, grading, charge, and multiplication avalanche photodiodes (SAGCM APDs) and study the effect of the charge layer and multiplication layer on the operating voltage ranges of APD. We find that with the increase of the thicknesses as well as the doping concentrations of the charge layer and the multiplication layer, the punchthrough voltage increases; with the increase of the doping concentrations of two layers and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Next, photocurrent–voltage characterizations were carried out by a continuous‐wave (CW) laser at 1310 nm, which allowed electron–hole pairs to be generated only in the GaSb absorbers. Clearly, the characteristics of photocurrent are different from those of InGaAs/InP or InGaAs/InAlAs SAM‐APDs . As shown in Figure a, we observe a two‐stage increase in photocurrent.…”
Section: Experiments Results and Discussionmentioning
confidence: 77%
“…Next, photocurrent–voltage characterizations were carried out by a continuous‐wave (CW) laser at 1310 nm, which allowed electron–hole pairs to be generated only in the GaSb absorbers. Clearly, the characteristics of photocurrent are different from those of InGaAs/InP or InGaAs/InAlAs SAM‐APDs . As shown in Figure a, we observe a two‐stage increase in photocurrent.…”
Section: Experiments Results and Discussionmentioning
confidence: 77%
“…For instance, the high electron-mobility transistors [1][2][3][4] and the spin field-effect transistors [5] are feasible electronic devices that could be demonstrated on InAlAs/InGaAs heterostructures. In addition, the infrared photodetectors [6][7][8][9], X-ray detectors [10], terahertz (THz) quantumcascade lasers [11,12], mid-infrared quantum-cascade lasers [13,14], and electro-optical modulators [15] are also typical examples that can open up a broad avenue toward the tangible optoelectronic applications of the InAlAs/InGaAs quantum well (QW) structures. When growing the epitaxial heterostructure, in general, both the alloy disorder and the layer-thickness fluctuation are inevitable because of the lattice mismatch in between the ultrathin heterojunction layers.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the charge layer of InAlAs APDs, Kleinow et al studied the influence of doping concentration in this layer and found that doping concentration is more important for the performance of InGaAs/InAlAs APDs [25, 26]. Chen et al studied the influence of the charge and multiplication layers on punch-through and breakdown voltages by theoretical analysis and simulation [27]. These studies have focused on the performance of InAlAs APDs under the linear model.…”
Section: Introductionmentioning
confidence: 99%